TINJAUAN KEPUASAN PASIEN DI PELAYANAN RAWAT JALAN TERHADAP WAKTU TUNGGU PENYEDIAAN BERKAS REKAM MEDIS DI RSU IMELDA PEKERJA INDONESIA MEDAN TAHUN 2019 - Marta Simanjuntak (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2020)
The outpatient registration place is the place where patients first met with the officer, ideally the average waiting time for record services is 10 minutes. The purpose of this study was conducted to determine patient satisfaction with the waiting time for the provision of medical records in RSU Imelda Workers Indonesia Medan. Methodology This research uses descriptive research method with a quantitative approach. The tools used were questionnaire and Likert scale. The population in this study were all outpatients. The sample size was 30 patients and the medical record file. Data analysis uses univariate analysis. The sampling technique uses accidental sampling. This research was conducted at the Imelda Indonesian Workers Hospital in Medan. From this study the results obtained by the time required by officers to provide medical record files are 11 medical record files (36.7%) right and 19 medical record files (63.3%) incorrect. The level of outpatient satisfaction based on 5 dimensions, namely the Responsiveness dimension, said 12 patients were satisfied (40%), the Reability dimension stated 19 patients were dissatisfied (63.3%), the Assurance dimension was satisfied as many as 15 patients (50%), the Emphaty dimension stated as many as 14 patients (46.7%), and Tangible dimensions stated that they were quite satisfied as many as 17 patients (56.7%). Conclusion, The level of patient satisfaction is mostly stated quite satisfied. Suggestions, It is necessary to improve the performance of health services from the Reability dimension through work culture efforts, such as the formation of a compact working group because they have received training in accordance with technological developments and community expectations, so that health care workers are responsive, timely and accurate in serving patients.